The Frequency of Risk Factors Associated with Pregnancy among Women Seeking Planned Pregnancy - Fatemeh Ghaffari Sardasht; Nahid Jahani Shourab; Farzaneh Jafarnejad; Hibibollah Esmaily (Mashhad University of Medical Sciences, 2017)
Background & aim: Pre-pregnancy period is like a window of hope during which the doctors and midwives can help the mothers to solve or adjust the problems needing special care before pregnancy. Therefore, this study was carried out to determine the risk factors for pregnancy health among the females seeking planned pregnancy. Methods: This descriptive study was conducted on 350 females of childbearing age who referred to health centers of Mashhad, Iran to receive preconception care in 2013. The sampling was performed using the multistage sampling technique. The data were collected by a researcher-made questionnaire enquiring the patients' demographic and obstetric data. Data analysis was performed through the SPSS version 16 using mean and standard deviation (for quantitative variables), frequency (for qualitative variables), and Chi-square test (to assess the relationship between the variables). P-value less than 0.05 was considered statistically significant. Results: According to the results, the age of 2% and 4.9% of the participants were < 18 and > 35 years, respectively. The most frequent risk factors for pregnancy health were related to gestational diabetes (32%), preeclampsia (22%), abortion (19.1%), history of vaginal bleeding in the second half of pregnancy, and preterm delivery (13%). In addition, the most frequent underlying diseases were diabetes mellitus (22%), thyroid disorders (22%), heart disease, as well as asthma and allergies (13%). Conclusion: As the findings of the present study indicated, most of the risk factors in the pre-pregnancy period were related to diabetes mellitus and gestational diabetes.